2022
DOI: 10.3390/ijms232214056
|View full text |Cite
|
Sign up to set email alerts
|

The rs1883832 Polymorphism (CD40-1C>T) Affects the Intensity of IgA Responses after BNT162b2 Vaccination

Abstract: The effectiveness of coronavirus disease 2019 (COVID-19) vaccination strategies is affected by several factors, including the genetic background of the host. In our study, we evaluated the contribution of the functional polymorphism rs1883832 affecting the Kozak sequence of the TNFSF5 gene (c.-1C>T), encoding CD40, to humoral immune responses after vaccination with the spike protein of SARS-CoV-2. The rs1883832 polymorphism was analyzed by PCR-RFLP in 476 individuals (male/female: 216/260, median age: 55.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…For example, polymorphisms of the tumor necrosis factor-α-related gene are strongly related to antibody production following COVID-19 vaccination and might be associated with different clinical conditions noted thereafter [ 4 ]. A similar observation was reported for the rs1883832 polymorphism (CD40-1C>T) and the variant alleles of ALDH2 and rs671 [ 5 , 6 ]. T and B lymphocyte phenotypes are also important predictors of the humoral response to COVID-19 vaccination in patients with end-stage renal illness [ 7 ].…”
supporting
confidence: 83%
“…For example, polymorphisms of the tumor necrosis factor-α-related gene are strongly related to antibody production following COVID-19 vaccination and might be associated with different clinical conditions noted thereafter [ 4 ]. A similar observation was reported for the rs1883832 polymorphism (CD40-1C>T) and the variant alleles of ALDH2 and rs671 [ 5 , 6 ]. T and B lymphocyte phenotypes are also important predictors of the humoral response to COVID-19 vaccination in patients with end-stage renal illness [ 7 ].…”
supporting
confidence: 83%
“…To the best of our knowledge, this is the first study analyzing the contribution of the CD40 -rs1883832 polymorphism with clinical presentation and severity of SARS-CoV-2 infection. Our group has recently reported that upon vaccination, this polymorphism affects the IgA antibody responses against SARS-CoV-2 [ 19 ], while it has also been correlated with a susceptibility to sepsis in a Chinese population [ 45 ]. However, we did not find a significant association between the CD40 -rs1883832 polymorphism and the clinical course of COVID-19 in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The sequences of the utilized primers, conditions of PCR reactions, and the restriction enzymes used for the detection of each SNP are shown in detail in Table 2 . It is worth noting that the primers for the detection of TLR2 -rs5743708, TLR4 -rs4986790, TLR4 -rs4986791, and CD40 -rs1883832 polymorphisms were previously reported by us and others in the literature [ 17 , 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…352 – 354 Functional investigations have shown that the disease-associated CD40 mutation modifies the consensus Kozak initiation sequence, increasing translational efficiency and pointing to a causal relationship between overexpression of CD40 and the propensity for Graves’ hyperthyroidism. 355 Indeed, evidence from a variety of murine models has disclosed that genetic or chemical manipulation of CD40 signaling can alter the severity of autoimmune thyroiditis or the generation of thyroid autoantibodies, designating CD40 as a promising target in the management of this condition. 351 , 352…”
Section: Hyperthyroidismmentioning
confidence: 99%